Pendekatan Humanistik Dalam Pengembangan Kurikulum Pendidikan Agama Islam - Cahyani Isnaini; Fitri Ayu; Abdul Malik; M. Safe’i Maulana; Sucipto Andika; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to determine the characteristics of a humanistic Islamic religious education curriculum as well as how the program evolved using a humanistic perspective. This study's methodology makes use of library research techniques (library study). This approach concentrates on using library resources to gather information for research projects. Meanwhile, content analysis is the method of data collecting employed in this study. A strategy for analyzing text, whether it be in the form of words, graphics, or another format, is content analysis. The findings of this study demonstrate that a humanistic approach was used in the creation of the Islamic religious education curriculum. Specifically, the humanistic notion of offering a fresh viewpoint in PAI learning, the qualities of ideal teachers, as well as